2001
DOI: 10.1067/mva.2001.117330
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of a polyurethaneurea vascular access graft as compared with the expanded polytetrafluoroethylene vascular access graft in hemodialysis applications

Abstract: The PVAG graft allows for early access without compromising long-term performance. Both PVAG and standard ePTFE grafts have similar long-term outcomes, despite early access with the PVAG vascular access grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 12 publications
9
90
1
1
Order By: Relevance
“…In contrast, immediate-use AVGs are made of polyurethane and include a special middle layer with a nonpermeable self-sealable coat that permits them to be safely cannulated within 24 hours of their placement (42). Under what circumstances is the use of immediate-use AVG justified?…”
Section: What Is the Role Of An Immediate-use Avg?mentioning
confidence: 99%
“…In contrast, immediate-use AVGs are made of polyurethane and include a special middle layer with a nonpermeable self-sealable coat that permits them to be safely cannulated within 24 hours of their placement (42). Under what circumstances is the use of immediate-use AVG justified?…”
Section: What Is the Role Of An Immediate-use Avg?mentioning
confidence: 99%
“…Glickman et al (9) reported 12-month primary and secondary patency rates between 78% and 85% compared with ePTFE grafts. Jefic et al …”
Section: Polyurethane Vascular Access Graftmentioning
confidence: 99%
“…Although the FFI philosophy encourages an AVF to replace every failed access, a high-risk patient (e.g., risk factors for CVC use and AVF failure) might have a forearm loop graft immediately placed, rather than proceed to an upper arm AVF, obviating the need for a CVC (33,72,(103)(104)(105). This would permit greater flow to veins, maturing the upper arm such that an AVF can be created when the graft fails rather than attempting to salvage it.…”
Section: Selectively Use Grafts: They Do Have a Placementioning
confidence: 99%